2008
DOI: 10.1002/app.27159
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane foams with 1,3‐pyrimidine ring

Abstract: Attempts of obtaining of polyurethane foams using polyetherols with 1,3-pyrimidine ring (obtained in reactions of 6-aminouracil with oxiranes) are reported. Properties of the foams are investigated, especially their thermal stability. The foams show an improved thermal stability up to 2008C for a long time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Apparent density of obtained foams was found in the range 24 95 kg/m 3 (Tab. 2) and it is similar to those for the foams prepared from polyetherols on the basis of oxiranes [1] and carbonates [2]. Water absorption after 24 hours exposition in water was in the range 7.9 22.4 wt.% (Tab.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Apparent density of obtained foams was found in the range 24 95 kg/m 3 (Tab. 2) and it is similar to those for the foams prepared from polyetherols on the basis of oxiranes [1] and carbonates [2]. Water absorption after 24 hours exposition in water was in the range 7.9 22.4 wt.% (Tab.…”
Section: Resultsmentioning
confidence: 54%
“…Thus that they can be useful polyol components and can applied to obtain polyurethane foams with improved thermal stability. Polyurethane foams synthesized from these polyetherols show better thermal stability than foams synthesized on the basis of polyetherols obtained in reaction of 6-AU with oxiranes [1] and similar to thermal stability of foams based on polyetherols synthesized from 6-AU and alkylene carbonates [2]. The foams obtained from polyetherol synthesized at lower temperature (140 o C) show higher compression strength than foams based on polyetherols obtained from 6-AU and alkylene carbonates [2].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been demonstrated that polyetherols with perhydro‐1,3,5‐triazine,1–3 1,3,5‐triazine,4–8 and purine9, 10 rings can be used as polyol components to obtain polyurethane foams with improved thermal stability. The foams with improved thermal stability can also be synthesized by the introduction of 1,3‐pyrimidine ring 11, 12. Polyetherols with 1,3‐pyrimidine ring have been obtained in reactions of 6‐aminouracil (6‐AU) with excess of oxiranes13 or alkylene carbonates 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Polyetherols with 1,3‐pyrimidine ring have been obtained in reactions of 6‐aminouracil (6‐AU) with excess of oxiranes13 or alkylene carbonates 14, 15. The foams synthesized from polyetherols obtained in reaction of 6‐AU with excess of oxiranes (especially propylene oxide, PO) show a very good thermal resistance (the mass loss was equal to 13% at 150°C and 37.5% at 200°C) and good compression strength (0.24 MPa at 10% deformation strain) 11. The foams synthesized from polyetherols obtained in reaction of 6‐AU with excess of alkylene carbonates (especially ethylene carbonate, EC) show lower mass loss than these mentioned earlier (6.9% at 150°C and 33.1% at 200°C), but the compression strength is lower (0.14 MPa at 10% deformation strain) 12.…”
Section: Introductionmentioning
confidence: 99%